2021
DOI: 10.48550/arxiv.2109.04059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The GALAH Survey: Chemical tagging and chrono-chemodynamics of accreted halo stars with GALAH+ DR3 and $Gaia$ eDR3

Sven Buder,
Karin Lind,
Melissa K. Ness
et al.

Abstract: Since the advent of Gaia astrometry, it is possible to identify massive accreted systems within the Galaxy through their unique dynamical signatures. One such system, Gaia-Sausage-Enceladus (GSE), appears to be an early "building block" given its virial mass > 10 10 M at infall (𝑧 ∼ 1 βˆ’ 3). In order to separate the progenitor population from the background stars, we investigate its chemical properties with up to 30 element abundances from the GALAH+ Survey Data Release 3 (DR3). To inform our choice of element… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 154 publications
(373 reference statements)
0
6
0
Order By: Relevance
“…Presumably, the halo shows this interesting residual variability and structure as it is comprised of stars from many different star formation environments (e.g. Scannapieco et al 2021;Naidu et al 2021;Bonaca et al 2020;Hallakoun & Maoz 2021;Ishigaki et al 2021;Naidu et al 2020;Buder et al 2021a). Note where some elements show large positive residuals, others show large negative residuals.…”
Section: The Holistic View Of Residual Scatter In the Milkymentioning
confidence: 97%
“…Presumably, the halo shows this interesting residual variability and structure as it is comprised of stars from many different star formation environments (e.g. Scannapieco et al 2021;Naidu et al 2021;Bonaca et al 2020;Hallakoun & Maoz 2021;Ishigaki et al 2021;Naidu et al 2020;Buder et al 2021a). Note where some elements show large positive residuals, others show large negative residuals.…”
Section: The Holistic View Of Residual Scatter In the Milkymentioning
confidence: 97%
“…A list of studies have shown that these disrupted stellar systems, together with globular clusters and chemically peculiar stars with halo orbits, can be grouped based on similar orbital properties, suggestive of their common origins (Roederer et al 2018;Myeong et al 2018b;Myeong et al 2019;Naidu et al 2020;Yuan et al 2020b;Bonaca et al 2021;Limberg et al 2021;Gudin et al 2021;Li et al 2021a;Shank et al 2021). Detailed abundance studies for these stellar debris have been made possible by HRspectroscopic follow-up studies (Ji et al 2020;Aguado et al 2021a,b;Matsuno et al 2021;Gull et al 2021), as well as by HR-spectroscopic surveys, such as the GALactic Archaeology with HERMES survey (GALAH; Buder et al 2021;Simpson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised learning methods have been used to define and study kinematic structures of galaxies (DomΓ©nech-Moral et al 2012;Obreja et al 2018Obreja et al , 2019Buck et al 2018Buck et al , 2019b or identify accreted stars from disrupted satellites of the MW (e.g. Buder et al 2021a) in the GALAH survey data (Buder et al 2021b). Hierarchical clustering on the other hand was employed to investigate the connection between stellar birth radii and their abundances (e.g.…”
Section: Introductionmentioning
confidence: 99%